Effects of Ilex paraguariensis on Redox Status in High-fat Diet Fed Mice - Xianghui LI; Ruixia LIU; Junfang ZHAO; Yuanyuan ZHANG; Jiao WANG (Shipin gongye ke-ji, 2022)
Objective: To investigate the effects of Ilex paraguariensis on redox status in high-fat diet fed mice. Methods: Forty-eight male C57BL/6J mice of six-week-old were randomly divided into 4 groups, normal diet (ND), high-fat diet (HF), high-fat diet+1 g/kg Ilex paraguariensis (HFL), high-fat diet+2 g/kg Ilex paraguariensis (HFH). The mice were sacrificed six weeks later. Hepatic redox status-related indicators were measured. The expression of FoxO3a, catalase and MnSOD genes in liver were analyzed. Results: Compared with the ND group, the levels of ROS and MDA in the liver of the HF group were increased significantly (P < 0.05), CAT, SOD, GSH-Px, GSH/GSSG values and T-AOC were reduced significantly (P < 0.05), the expression of FoxO3a, catalase and MnSOD genes in the liver were decreased significantly (P < 0.05). Compared with the HF group, the levels of ROS and MDA in the liver of the HFL and HFH groups were reduced significantly (P < 0.05), CAT, SOD, GSH-Px, GSH/GSSG values and T-AOC were increased significantly (P < 0.05), the expression of FoxO3a, catalase and MnSOD genes in the liver were increased significantly (P < 0.05). Correlation analysis showed that ROS and FoxO3a, catalase, MnSOD genes expression were significantly negative correlation (P < 0.01), CAT, SOD, GSH-Px and FoxO3a, catalase, MnSOD genes expression were significantly positive correlation (P < 0.01). Conclusion: Appropriate amount of Ilex paraguariensis can improve the redox state imbalance of mice caused by high-fat diet, which has a certain relationship with FoxO3a gene pathway.